Совершенствование среднечастотного селективного алгоритма поиска поврежденного участка сети при замыканиях на землю. Часть 1. Совершенствование критериев работы - Никифоров, Андрей Петрович (НТУ "ХПИ", 2010)
Search of the damaged site of a network at short circuits on the ground. Part 1. Perfection of criteria of work. Part 2. Perfection of the device of selective searchThe application of structural-information method for the synthesis of stable working devices selective search the damaged portion of the distribution network for insulation damage on the ground. The most selective criterion selected midrange, allowing working in any type of neutral grounding network medium voltage class. Easy to use structural information of the method, simulation of the synthesized device and test devices fabricated to characterize the method as an effective and apply it to a wider range of tasks.
Perfection of mid-frequency selective algorithm
Keywords: электродвигатель высоковольтный; изоляция фаз; поиск селективный; контур нулевой последовательности сети; НЧС-критерий; стабилизация автоматическая; символ терминальный; СЧС-критерий